Citoyens, piété et démocratie. Réflexions sur l'occultation des corps croyants, l'intimité et le droit au secret - Amiraux, Valérie (Social compass, 2018)
This article is based on ongoing fieldwork conducted in France and Quebec with Muslim women who stopped wearing a headscarf. It offers a puzzle for reflection: what is achieved when a sign of religious affiliation disappears (in this instance, wearing a headscarf)? The first part of the article describes the general framework in which public conversations about the visible piety expressed by Muslim women has been discussed in public spaces. The second part looks at the double bind in which Muslim women have been placed by being asked, on the one hand, to be as discrete as possible when expressing their religiosity and, on the other, to behave in full transparency. How and under which conditions can these women find a place' in the public space (Joseph, 1995) of secular societies? To conclude, the article invites reflection on the role of secrecy, the impossibility as well as the necessity of the secret in society in order to be able to consider the proper room available for pious female citizens in democratic secular societies.